Prevalence and influencing factors of hazardous drinking among residents in northern China, 2010: a cross-sectional survey - Hui ZHANG; Xue LI; Ya-chao LI (Editorial Office of Chinese Journal of Public Health, 2023)
Objective To examine the prevalence and risk factors of hazardous drinking behavior among residents in northern China for providing evidence to the implementation of mental health care in populations with hazardous drinking behavior. Methods An on-site self-administered questionnaire survey was conducted among 6 087 community residents at ages of 16 years and above recruited in northern China (Beijing municipality, Harbin city of Heilongjiang province, and Karamay city of Xinjiang Uygur Autonomous Region) using probability proportionate to size sampling during October 2010. In addition to a self-designed questionnaire, the Alcohol Use Disorders Identification Test (AUDIT), Self-Rated Health Measurement Scale (SRHMS), Patient Health Questionnaire (PHQ), Ways of Coping Questionnaire (WCQ), and other relevant scales were adopted in the survey. Results Of the 5 972 participants completing the survey effectively, 1 886 (31.58%) reported alcohol drinking; 785 (13.14%) were assessed as with hazardous drinking, accounting for 41.62% of all alcohol drinkers identified. Unconditional multivariate logistic regression analysis revealed following risk factors of hazardous drinking for the participants: at ages of 31 - 50 years, living in Harbin or Karamay city, being administrative personnel or personnel other than technician/salesman, with family monthly income ≥ 1 500 yuan (RMB) per capita, positive for depression symptoms, positive for anxiety symptoms, and with a high score of negative coping style; while, female gender and with a high score of mental health were protective factors against hazardous drinking. ConclusionThe prevalence of hazardous drinking was high and mainly influenced by gender, age, region, occupation, family monthly income per capita, mental health score, depressive symptom, anxiety symptom and negative coping style among community residents in the northern China.